2024
DOI: 10.1007/s11259-024-10369-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in South American camelids presented at a farm animal clinic in Northern Germany (2005–2021)

Saskia Neubert,
Christina Puff,
Sven Kleinschmidt
et al.

Abstract: To expand the knowledge about common diseases in llamas and alpacas in Germany, a screening of the cases of South American camelids presented at the Clinic for Swine and Small Ruminants of the University of Veterinary Medicine Hannover, Germany from 2005 to the end of November 2021 was performed. A retrospective evaluation of necropsy reports from this period was conducted. Overall, necropsy reports were evaluated from 187 alpacas, 35 llamas and one vicuña (n = 223). A total of 50.2% of the dissected animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
1
0
1
Order By: Relevance
“…A low nutritional status is a common problem in SACs and can be attributed to chronic infectious diseases, endoparasites, dental problems or poor feeding management [ 45 ]. A retrospective study of necropsy data from SACs presented to our clinic over a 16-year period showed that more than half of the animals were thin or cachectic, which often went undetected for a long time [ 46 ]. Therefore, regular examination of the BCS by the owner is recommended to detect emaciated alpacas and llamas in time.…”
Section: Discussionmentioning
confidence: 99%
“…A low nutritional status is a common problem in SACs and can be attributed to chronic infectious diseases, endoparasites, dental problems or poor feeding management [ 45 ]. A retrospective study of necropsy data from SACs presented to our clinic over a 16-year period showed that more than half of the animals were thin or cachectic, which often went undetected for a long time [ 46 ]. Therefore, regular examination of the BCS by the owner is recommended to detect emaciated alpacas and llamas in time.…”
Section: Discussionmentioning
confidence: 99%
“…Der genaue Zeitrahmen für das Schließen des Ductus arteriosus bei neugeborenen Kameliden ist nicht bekannt, es wird aber vermutet, dass dieser Verschluss bis zu 72 Stunden post partum dauern kann [28]. Auswertungen von Sektionsdaten von Neuweltkamelen aus der Klinik für kleine Klauentiere zeigten bei 2 Tieren eine beidseitige Choanenatresie, die mit dem Fehlen der Bulbi olfactorii assoziiert war [29]. In Anbetracht möglicher weiterer Missbildungen sollte eine chirurgische Therapie betroffener Tiere kritisch evaluiert werden.…”
Section: Bei Offenenunclassified